THE PROBLEM OF THE NAFS IN LITERATURE - Sanobar Tulaganova (Modern American Journals, 2025)
This article analyzes the artistic expression of the concept of nafs (the self, or ego) and its philosophical-spiritual interpretation in the works of Abdulla Qodiriy. Based on examples from the novel “Bygone Days” (O‘tkan kunlar), the study examines the author’s use of the expression “to dedicate one’s nafs”, through which Qodiriy conveys Islamic and Sufi worldviews in artistic form. The novel depicts different levels of the nafs (ammara, lawwama, mutmainna) through its characters, reflecting the inner spiritual struggle of an individual on the path toward perfection. The research employs Sufi, Sharia-based, and psychoanalytic approaches to explain the moral and spiritual essence of the nafs in the artistic context.
Keywords: Nafs, soul, Sufism, nafs al-ammara, nafs al-mutmainna, Abdulla Qodiriy, psychological analysis, Jadidism, psychoanalysis.